1998
DOI: 10.1046/j.1460-9568.1998.00065.x
|View full text |Cite
|
Sign up to set email alerts
|

Influence of acetylcholinesterase on embryonic spinal rat motoneurones growth in culture: a quantitative morphometric study

Abstract: Rat spinal motoneurones sampled at day embryonic 15 were purified using a Nycodenz gradient and cultured in defined medium, during 7 days, on glass coverslips coated with poly-L-lysine and laminine. Purified acetylcholinesterase (AChE), ecothiopate, BW 284C51 and fasciculin II, inhibitors of either the catalytic or peripheral site of AChE, were added to the defined medium. Morphological changes of spinal motoneurones were measured using a statistical quantitative morphometric method, allowing the determination… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
42
0
1

Year Published

1999
1999
2015
2015

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 57 publications
(44 citation statements)
references
References 49 publications
1
42
0
1
Order By: Relevance
“…TAN (Massman et al, 1996); motor neurons comprise part of the "global cell population." Indeed, the common pathological association for the Alzheimer's and Parkinson' disease is also demonstrated for the motor neurons (Bataille et al, 1998). Accordingly, Greenfield and Vaux (2002) proposed that these three major neurodegenerative disorders can be associated by a common mechanism.…”
Section: Motor Neuron Disease (Mnd)mentioning
confidence: 99%
“…TAN (Massman et al, 1996); motor neurons comprise part of the "global cell population." Indeed, the common pathological association for the Alzheimer's and Parkinson' disease is also demonstrated for the motor neurons (Bataille et al, 1998). Accordingly, Greenfield and Vaux (2002) proposed that these three major neurodegenerative disorders can be associated by a common mechanism.…”
Section: Motor Neuron Disease (Mnd)mentioning
confidence: 99%
“…Because of the existence of a diffuse projection from brain stem origins to the remote areas of the brain and spinal cord, Woolf (1996) introduced the term "global neurons".This system might be extended to motor neuron disease, which can, like Parkinson`s disease, co-exits with Alzheimer-like features (Massman et al, 1996); motor neurons comprise part of the "global cell population". Indeed, the common pathological association for the Alzheimer`s and Parkinson` disease is also demonstrated for the motor neurons (Bataille et al, 1998). Accordingly, Greenfield and Vaux (2002) proposed that these three major neurodegenerative disorders can be associated by a common mechanism.…”
Section: Motor Neuron Disease (Mnd)mentioning
confidence: 99%
“…To estimate the impact of viral infection on cellular metabolism, we compared, by quantitative morphometry, the growth of the longest neurite (that can be considered as the axon) in infected and noninfected MNs during 7 days. A previous study had shown that, among several morphometric criteria, the axon length was the parameter that increased the most dramatically during 7 days of culture (Bataillé et al, 1998). Individual MNs in low density cultures, infected or noninfected with RV, were photographed daily during 7 consecutive days and the length of their longest neurite was measured ( Figure 5A).…”
Section: Neurite Growth In Mns Infected With Rvmentioning
confidence: 99%
“…The cultures were prepared from pregnant Wistar rats at 15 days of gestation (Centre d'Élevage et de Recherche Janvier, France) according to the technique described by Bataillé et al (1998). The rst steps were common for both preparations.…”
Section: Preparation Of Cultures Of Crude Spinal Cord or Of Puri Ed Mmentioning
confidence: 99%
See 1 more Smart Citation